Written culture: learning how to read and write in school - Doris Pires Vargas Bolzan; Eliane Aparecida Galvão dos Santos; Ana Carla Hollweg Powaczuk (Universidade Federal de Santa Maria, 2013)
This paper discusses the formal aspects of writing and reading within the classroom context, emphasizing the importance of the students' role, favoring their authorship as writers and readers from written culture. We understand that it is indispensable that the school beholds a prospective view in relation to the students' learning, taking their ideas and constructions into consideration; that is, bearing in mind the culture of which they are carriers. We highlight the literacy teacher's role in the process of organizing the pedagogical work that is aimed at teaching and learning reading and writing for the students that are in the early years of elementary school. In this way, we point out that the organization of the teaching requires teaching investment towards the improvement of activities and knowledge that focus on the organization of the pedagogical work, marking a long path to go to allow the assumption of pedagogical protagonism.